Prevalence of rotavirus and adenovirus associated with diarrhea among displaced communities in Khartoum, Sudan - Elhag, Wafa I (BioMed Central, 2013)
BACKGROUND: Diarrheal diseases represent a major worldwide public health problem particularly in developing countries. Each year, at least four million children under five years of age die from diarrhea. Rotavirus, enteric adenovirus and some bacterial species are the most common identified infectious agents responsible for diarrhea in young children worldwide. This study was conducted to determine prevalence of rotavirus and adenovirus associated with diarrhea among displaced communities in Khartoum state, Sudan. METHODS: A total of seven hundred and ten patients, children and adults, suffering from diarrhea were examined. The clinical history, socio-demographic characteristics, physical examination findings and laboratory investigations were recorded. Stool samples or rectal swabs were collected and tested for rotavirus and adenovirus antigens using the immuno-chromatography test (ICT). Characterization of the identified Rotaviruses, as a major cause of diarrhea, was then made using real time-reverse transcription PCR. To make the study legal, an ethical clearance was obtained from Sudan Ministry of health- Research Ethical Committee. Written consent was taken from adult subjects, and also from children mothers. The participants were informed using simple language about the infection, aim of the research and the benefits of the study. RESULTS: Out of the 710 patients, viral pathogens were detected in only 99 cases (13.9%). Of the 99 cases of viral diarrhea, 83 (83.8%) were due to rotaviruses while 16 (16.2%) attributed to adenovirus. Of the 83 rotaviruses identified, 42 were characterized by RT-PCR, of these 40 (95.2%) were proved as type A (VP6), and 2 (4.8%) type C (VP7). Type C (VP7) rotavirus was detected in samples collected from children under 5years only. CONCLUSIONS: In conclusion, most cases of viral diarrhea are found to be caused by rotavirus especially among children less than five years. Most of the identified rotavirus belonged to type A (VP6). It was also evident that most patients are those who drank untreated water obtained from donkey carts source and who had no access to latrines, and lived in poor environmental conditions would acquire diarrheal infection.